Transducin-Like Enhancer of Split-1 Inhibits Malignant Behaviors in vitro and Predicts a Better Prognosis in Pancreatic Ductal Adenocarcinoma - Wang, Yizhi; Yuan, Da; Zhou, Li; Liang, Zhiyong; Zhou, Weixun; Lu, Jun; Jiang, Bolun; You, Lei; Guo, Junchao; Zhao, Yu-Pei (Frontiers in Oncology, 2020)
Background: TLE1, a member of the Groucho/TLE family of transcriptional corepressors, has been reported to be involved in the tumorigenesis of various cancers and function as a clinical prognostic indicator. However, the mechanisms and prognostic significance of TLE1 in PDAC have not been elucidated. Methods: In this study, western blot analyses and RT-PCR were employed to evaluate the expression of TLE1 and related proteins in PDAC cell lines. Wound healing, transwell migration and invasion, and CCK-8 assays were used to determine cell line-specific differences in metastasis and proliferation. Flow cytometry was performed for cell cycle detection. RNA sequencing and bioinformatics were undertaken to explore the molecular mechanisms and potential targeted molecules of TLE1. TLE1 expression in tumor and para-tumor tissues was evaluated by tissue microarray-based immunohistochemistry using a semiquantitative method (H-score) in 262 patients with radical PDAC resection. Correlation, Kaplan-Meier survival, univariate, and multivariate analyses were also performed. Results: Our findings showed that TLE1 expression was common in PDAC cell lines. Upregulation of TLE1 inhibited PDAC cell migration, invasion and proliferation in vitro by delaying the G0/G1 transition. Immunohistochemistry revealed that TLE1 was specifically expressed in the nucleus and at higher levels in tumor tissues compared with para-tumor tissues. Generally, high TLE1 expression was associated with no vascular invasion. In univariate analyses, high TLE1 expression was associated with longer DSS in all patients and in 16 patient subgroups. In multivariate analysis, TLE1 expression was independently associated with DSS in all patients and four patient subgroups. Conclusion: In conclusion, these results suggest that TLE1 has an inhibitory role in PDAC progression and is a favorable prognostic indicator for patients with resectable PDAC.